Path Analysis in Cluster Bean[Cyamopsis tetragonoloba (L.) Taub.]Genotypes For Vegetable Pod Yield (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
An experiment was conducted on 30 cluster bean genotypes to study the path analysis among the vegetable pod yield and their direct and indirect effects on the pod yield. This study helps in identifying the characters which mainly contributing towards vegetable pod yield. Using path analysis, it is possible to resolve the correlations, which will provide direct and indirect contribution of different morphological and yield and yield contributing characters. Path analysis identified characters such as days taken for first flowering, days taken for 50% flowering, number of pods/plant, number of pods/cluster, number of clusters/plant, number of branches/plant at maturity, number of seeds/pod, pod yield/plant and pod yield/plot showed significant and positive direct effects on the pod yield (q/ha) at genotypic path coefficient analysis. Path analysis identified characters such as number of reproductive branches/plant, pod length, pod width, number of pods/cluster, number of branches/plant at maturity, number of seeds/pod, pod yield/plot, 100- seed weight and seed yield/plant showed significant and positive direct effects on pod yield (q/ha) at phenotypic path coefficient analysis. Thus present path analysis study in cluster bean, it may be concluded that improvement in pod yield/ha could be brought by selection for component characters like days to 50% flowering, pods/cluster, pod length, number of seeds/pod and pod yield/plant.
Keywords: Path analysis; cluster bean; Cyamopsis tetragonoloba; genotypes; indirect effect and pod yield